Bibliometric Analysis of the Common Agricultural Policy: Intersections of Agriculture, Economy, and Environment - Cătălin Valentin LĂPĂDAT; Roxana Maria BĂDÎRCEA; Alina Georgiana MANTA; Alexandra Ioana GEORGESCU (Finanţe: Provocările viitorului)
This study explores the trends and limitations of research on the Common Agricultural Policy (CAP) in relation to agriculture, economy, and the environment, using a bibliometric analysis based on Web of science data. Employing co-citation maps and collaborative networks among authors and institutions, the study highlights a fragmented literature characterized by high thematic specialization and a low level of interconnectedness among researchers, hindering the development of a coherent and integrated framework. A detailed analysis of author collaborations and co-citation networks provides a clear view of the intellectual structure of the field and the ways ideas and research have been interconnected and developed over time. Additionally, the examination of highly cited articles and works has revealed not only the current gaps in research but also opportunities for future investigations. For instance, most studies have focused on the effects of Common Agricultural Policy (CAP) funding on the environment, biodiversity, farmer behaviour, and the economic outcomes of the agricultural sector. However, they have largely overlooked a comprehensive understanding of how these interactions simultaneously influence all three dimensions: economic, environmental, and agricultural. This highlights a significant opportunity for research to explore more complex and integrated connections between CAP funding and its impact on these three pillars, considering the recent evolution and changes in the global economic landscape.